Semantic Urgency and Illusion of Authority in Phishing Emails: A Corpus-Based Analysis - Rossy Halimatun Rosyidah (Journal of Linguistics, Literature, and Language Teaching (JLLLT), 2025)
This study examines how urgency and authority are semantically framed in phishing emails to manipulate recipients’ behavior. Although linguistic features of deception have been widely studied, the semantic framing of phishing remains underexplored within the Frame Semantics framework. Using qualitative frame-semantic discourse analysis, ten phishing emails were purposively selected from the open-access corpus by Miltchev et al. (2024), focusing on scams related to account access and payment issues. The data were analyzed through Fillmore’s Frame Semantics to identify lexical units and frame elements (e.g., Agent, Goal, Instrument) that trigger urgency and authority. Results show that phishing messages use time-sensitive cues (e.g., immediately, within 24 hours) and institutional references (e.g., your account, verify your identity) to create a sense of crisis and compel compliance. These frames often co-occur, increasing cognitive pressure and reducing critical evaluation. By mapping manipulative strategies onto semantic frames such as Request, Threat scenario, and Commerce transfer, this study provides a structured approach to phishing analysis. It contributes to cyber linguistics and supports the development of frame-aware digital literacy, email security systems, and spam detection models based on semantic cues.